Current topics in developmental biology. - Capco, David G. (David George) (Current topics in developmental biology, 1996)
The cytoskeleton is central to cell biology and is instrumental in developmental events. Volume 31 is divided into two major sections: nonchordate development and chordate development. Summaries of each section compare evolutionary conservation among organisms.